Toward Economic Development: The Evolution of NSF's Experimental Program to Stimulate Competitive Research (EPSCoR) - Hauger, J. Scott (Economic Development Quarterly, 2004)
Part of a special issue on science- and technology-based economic development. The writer traces the evolution of the Experimental Program to Stimulate Competitive Research (EPSCoR), demonstrating why state governments have had rational incentives to use EPSCoR to serve an economic development agenda. He examines how the institutions erected to govern it inadvertently allowed EPSCoR states to incorporate economic development as a motivating force. He also documents the growing economic development orientation of successful EPSCoR proposals and programs.